Primary Aldosteronism (Conn's Syndrome) - Xayrullayevna, Djurayeva Ra’no (American Journal of Bioscience and Clinical Integrity, 2024)
Primary aldosteronism is a disorder caused by autonomous production of aldosterone by the adrenal cortex (due to hyperplasia, adenoma, or carcinoma). Symptoms and signs include episodic weakness, elevated blood pressure, and hypokalemia. Diagnosis includes measurement of plasma aldosterone levels and plasma renin activity. Treatment depends on cause. A tumor is removed if possible; in hyperplasia, spironolactone or related drugs may normalize blood pressure and eliminate other clinical features.